252 EXPANSION OF THE ORTHOGERIATRIC SERVICE: EARLY EXPERIENCES. (18th November 2021) - Stankard, A; Conlon, B; O'Brien, H
Abstract: Background: The introduction of hip fracture standards has led to improvement in outcomes for hip fracture patients. Other osteoporotic fragility fractures also lead to significant morbidity. They are associated with a high risk of future hip fracture. The Orthogeriatric Service at a model 3 hospital was expanded to proactively undertake comprehensive geriatric assessment(CGA) for patients over 65 with non-hip fragility fractures(NHFF) admitted to the Orthopaedic Ward. Electronic discharge summaries were created for all patients. This study aimed to characterise patients reviewed by Orthogeriatrics and review discharge summary documentation of CGA. Methods: Patients reviewed by Orthogeriatrics during the period Jan-June 2021 were retrospectively analysed. Discharge summaries of these patients were retrospectively reviewed. The prevalence of documentation of frailty status, delirium screening and bone health plan was recorded. Results: A total(n = 126) of 91 patients with hip fractures and 35 with NHFF were included. Other fracture types were excluded. The mean age of hip fracture patients was 82.43 compared to 78.2 in the NHFF group. 71%(n = 65) of hip fracture patients were female compared to 80% (n = 28) of NHFF. 80%(n = 73) of hip fracture patients were reviewed within 48 hours of admission, compared to 65%(n = 23) of NHFF. 52.7%(n = 48)of hip fracture patients had frailty status documented on their discharge summary, compared to 37.1%(n = 13) of NHFF. Delirium screening was documented for 58.2%(n = 53) of the hip fracture patients, compared to 40%(n = 14) of NHFF. Bone health plans were documented for 62.6%(n = 57) of hip fracture patients compared to 60%(n = 21) of NHFF. Conclusion: Expansion of the Orthogeriatric Service to proactively review all NHFF patients will lead to reduced incidence of repeat fracture for this population. A lower percentage of NHFF patients had clear discharge documentation of CGA outcomes and a lower percentage were reviewed within 48 hours. Expansion of hip fracture standards to include all fragility fracture patients should be considered to incentivise improved care for all.